A goal programming approach for food product distribution / Maziah Rashidah Mohd Ramzi, Nurul Asyikin Mohamad Asri and Nur Maziah Che Md Kari - Mohd Ramzi, Maziah Rashidah; Mohamad Asri, Nurul Asyikin; Che Md Kari, Nur Maziah (2019)
Small and Medium Enterprise (SME) is now prominent industry in Malaysia. In general, the demand for traditional food is expected to increase in the future since there are many people still do not know how to make it. Traditional food product is unable to fulfil the customer's need despite the high demand due to certain limiting factors. Therefore, this research will apply a goal programming method in order to optimize the consumer's demands of traditional food in Senawang, Paroi, Seremban and Kuala Pilah. This research presents a goal programming model is to formulate with three objectives. Then, LINGO Software is then being used to test the model. The result shows that the objectives were fully achieved, and this proves that goal programming approach is a useful tool.